2001
DOI: 10.1097/00002030-200107270-00006
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the effectiveness of triple combination therapy in antiretroviral-naive HIV-1 infected adults

Abstract: The results suggest that three drug regimens containing two NRTI with a PI, a NNRTI, or a third NRTI may provide comparable activity, and practical issues such as daily pill burden should be considered when choosing a treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
219
3
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(239 citation statements)
references
References 15 publications
12
219
3
5
Order By: Relevance
“…Immunologic outcomes were good: the mean CD4+ Tcell count increase after one year was 236/mm 3 ; previous studies showed increases in mean CD4+ T-cell counts ranging from 127/mm 3 to 165/mm 3 [5,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunologic outcomes were good: the mean CD4+ Tcell count increase after one year was 236/mm 3 ; previous studies showed increases in mean CD4+ T-cell counts ranging from 127/mm 3 to 165/mm 3 [5,[8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…These results compare well to the results of HAART in other settings. A historical meta-analysis of clinical trials on NNRTI-based triple combination therapy in antiretroviral-naïve patients in western settings showed a plasma HIV-RNA level lower than 50 copies/ml after 48 weeks of treatment in 51% of patients (ITT) [5]. An on-treatment analysis in a recent study on HAART in subSahara Africa showed a plasma HIV-RNA level lower than 50 copies/ml in 61% of patients after 48 weeks of therapy (ITT 55%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate or inconsistent medication intake is a concern for health care providers, who are aware of the side effects and lifestyle changes required for their patients to take these medications. Research shows that medication-taking difficulties can be due to medication-related factors such as pill burden, side effects, and complicated regimens (Bartlett et al 2001;Fogarty et al 2002;. As new generations of drugs become available, pharmaceutical companies are addressing these concerns by developing pills that include more than one drug and regimen schedules that offer once or twice per day dosing with fewer and smaller pills.…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 PR contains a homodimeric C-2 symmetric structure and each monomer contributes one catalytic aspartic residue along with threonine and glycine residues which are flexible and a flap that favors the binding of substrate and inhibitors. The highly active antiretroviral therapy (HAART) and protease inhibitors (PIs) along with reverse-transcriptase inhibitors have resulted in the unprecedented success of HIV/AIDS chemotherapy [9][10][11][12]. However owing to the rapid emergence of drug-resistant HIV-1 variants and transmission of these resistant viral strains along with the adverse side effects of currently used HIV-1 PIs, are remain critical factors that limiting the clinical effectiveness of HAART [13][14][15].…”
Section: Introductionmentioning
confidence: 99%